Impact of 2009 Amnesty Programme on Youth Development in the Niger Delta (Global Journal of Human-Social Science, 2022)
The amnesty programme was proclaimed by the then-president Umaru Ya adua in June 2009 to grant pardon to all persons who directly or indirectly participated in militant activities in the Niger Delta region and were willing to surrender their weapons and renounce armed struggle against the federal government The amnesty programme sought to disarm demobilize integrate the repentant militants into the society through skill acquisition human capital development financial empowerment micro-credit facility and placement programme which had started and is ongoing This work seeks to ascertain the impact of the amnesty programme on the youth and development of the Niger Delta Region It adapts the historical approach and its materials were derived from secondary services The study also adopts the resource curse theoretical framework Finding from the study shows that environmental despoliation destruction of land and Rivers creeks in the area render the traditional occupation of farming and fishing impossible hardship on the people unemployment disease and death as a result of activities of oil multinational companies have not been addressed The study then recommends environmental mitigations and rejuvenation repeal of obnoxious oil industry laws timely release of funds for the programme assuage the youths from further militant activities in the Region